PENDAMPINGAN BACA TULIS AL-QUR’AN PADA SISWA SEKOLAH DASAR MELALUI KEGIATAN ROAD TO TPA NAGARI TANJUNG BARULAK - Safrizal, Safrizal; Libraniati, Ringga; Ratna Sari, Bunga; Arafat Lubis, Maulana; Azizan, Nashran (ALAINA: Jurnal Pengabdian Masyarakat, 2025)
The implementation of the value of reading and writing the Qur'an in elementary school children is an important effort in forming a generation that is moral and knowledgeable. The "Road To TPA" activity in Nagari Tanjung Barulak aims to improve the ability to read and write the Qur'an among children through community service methods. This program is implemented with an interactive and fun approach, involving the community and parents in the learning process. The evaluation results showed a significant increase in the ability to read and write the Qur'an of the children involved. In addition, this activity also contributes to the development of children's character, where they learn the ethical and moral values ​​contained in the Qur'an. The involvement of parents and the community is a crucial supporting factor, thus creating a conducive environment for learning. However, this program also faces several challenges, such as variations in learning progress among children and the need for consistency in learning. Therefore, it is advisable to hold a follow-up program that can ensure the sustainability of the literacy skills that have been obtained. Overall, the "Road To TPA" activity shows great potential in increasing Al-Qur'an literacy among elementary school children and can be used as a model for similar activities in other areas.